Petrografic pecularities and typisation of subalkaline dolerite-diabasic dike complexes of Ukrainian and Baltic Shields - MYTROKHYN, O.; OMELCHENKO, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The spatial and temporal locating of proterozoic subalkaline dolerite-diabasic dike complexes generated at a final stage of stabilization of the East Europe Craton are investigated by the example of the Ukrainian and Baltic Shields. The connection of the dike complexes with rapakivi-granite plutones together with trachybasalt-trachyriolites of rifting affinities are established. Abjection of a subalkaline dolerite-diabasic association is proved and its display features are revealed.